2003
DOI: 10.1046/j.1469-7580.2003.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrapopulation variability in mineralization density at the human femoral mid‐shaft

Abstract: One of several microstructural variables known to affect the mechanical properties of bone is the degree of mineralization of bone matrix. The aim of this study was to examine mineralization density, and its variability with age and sex, from a biomechanical perspective. Histological sections, prepared from mid-shaft femora obtained at autopsy from 40 individuals, were imaged using quantitative backscattered electron microscopy. Each cross-section montage was divided into 48 segments according to anatomical po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…At least two other studies have evaluated bone mineral heterogeneity. Goldman et al reported there was a significant increase in mineral heterogeneity in the midfemoral cortex among 45-64 year old females and males [29]. Other investigators reported an overall reduction in the mineralization, crystallinity and type-B carbonation in males aged 60 years or older, indicating a reduction in heterogeneity with aging [30].…”
Section: Discussionmentioning
confidence: 97%
“…At least two other studies have evaluated bone mineral heterogeneity. Goldman et al reported there was a significant increase in mineral heterogeneity in the midfemoral cortex among 45-64 year old females and males [29]. Other investigators reported an overall reduction in the mineralization, crystallinity and type-B carbonation in males aged 60 years or older, indicating a reduction in heterogeneity with aging [30].…”
Section: Discussionmentioning
confidence: 97%
“…via previous proposals, lessen damageability. In addition, mineralization of mature bone has been shown in some studies to decrease or remain unchanged with age (Thompson, 1980;Yeni et al, 1998;Currey, 1979;Currey et al, 1996;Goldman et al, 2003) while microdamage has been shown to increase with age (Schaffler et al, 1995;Norman and Wang, 1997;Fazzalari et al, 1998;Zioupos, 2001a, b). Thus, it would appear that there may be competing biological processes affecting tissue quality and the outcome of elevation or suppression of intracortical remodeling on bone damage accumulation.…”
Section: Introductionmentioning
confidence: 96%
“…The available data on bone turnover rates is mainly derived from measuring the uptake of 14 C in body tissues following the ''bomb peak'' of the late 1950s and early 1960s (Libby et al, 1964; Baxter, 1977, 1979;Wild et al, 2000;Geyh, 2001). The individual replacement rates are difficult to estimate, as they depend on various factors including health and nutrition (Oelbermann and Scheu, 2002;Voigt and Matt, 2004; Metoka et al, 2006), physical activity (Frost, 1988) as well as age and sex (Goldman et al, 2003;David et al, 2005). Furthermore, replacement rates vary between different types of bone tissue (compact or trabecular bone) and consequently between different skeletal elements (Sealy et al, 1995).…”
mentioning
confidence: 98%